1998
DOI: 10.1177/002215549804600104
|View full text |Cite
|
Sign up to set email alerts
|

Agrin Is a Major Heparan Sulfate Proteoglycan in the Human Glomerular Basement Membrane

Abstract: Agrin is a heparan sulfate proteoglycan (HSPG) that is highly concentrated in the synaptic basal lamina at the neuromuscular junction (NMJ). Agrin-like immunoreactivity is also detected outside the NMJ. Here we show that agrin is a major HSPG component of the human glomerular basement membrane (GBM). This is in addition to perlecan, a previously characterized HSPG of basement membranes. Antibodies against agrin and against an unidentified GBM HSPG produced a strong staining of the GBM and the NMJ, different fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
0
4

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(111 citation statements)
references
References 40 publications
4
103
0
4
Order By: Relevance
“…1c). These results indicate that the decreased staining of the GBM by antiheparan sulphate antibody JM403 is not due to reduced synthesis of the core protein of agrin, which is the major heparan sulphate proteoglycan in the GBM [24,25]. In this analysis we also observed an inverse correlation between the heparan sulphate domain content of the GBM and the level of proteinuria (Fig.…”
Section: Resultssupporting
confidence: 66%
“…1c). These results indicate that the decreased staining of the GBM by antiheparan sulphate antibody JM403 is not due to reduced synthesis of the core protein of agrin, which is the major heparan sulphate proteoglycan in the GBM [24,25]. In this analysis we also observed an inverse correlation between the heparan sulphate domain content of the GBM and the level of proteinuria (Fig.…”
Section: Resultssupporting
confidence: 66%
“…54 Furthermore, agrin is a major heparan sulfate proteoglycan in the adult GBM. 17,55 The anionic heparan sulfate side chains of agrin play an important role in the maintenance of the charge-dependent permeability of the GBM. 56 -58 In the present study, we observed a difference in ultrastructural localization between the N-and C-terminus of agrin.…”
Section: Discussionmentioning
confidence: 99%
“…22,23,40 In contrast, N-terminal antibodies label glomerular, tubular, and vascular smooth muscle BMs uniformly. 40 The reason for this discrepancy is unknown, but it might reflect alternative splicing or processing of agrin.…”
Section: Agrn Knockout Mice Synthesize N-terminal Truncated Forms Of mentioning
confidence: 96%
“…21 Agrin has been identified as the predominant GBM-HSPG in all species studied, prompting speculation that it may be a critical determinant of the charge barrier. 22,23 It is characterized by an ϳ2000-residue core protein of ϳ220 kd that carries at least two GAG chains, bringing its mass to ϳ400 kd. Agrin is generally classified as an HSPG, but it can carry both heparan and chondroitin sulfate (CS) GAGs.…”
mentioning
confidence: 99%